AN ANALYSIS ON JAVANESE LANGUAGE COMPOUNDING FOUND IN PANJEBAR SEMANGAT MAGAZINE - RAZANAH, HASYYATI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Morphology, Word formation process, compounding, Javanese language, Panjebar Semangat.In this study, the writer conducts a study of Javanese language compounding in Panjebar Semangat magazine. It is focuses on cerkak rubric. There are two research problems to be solved: (1) what are the component structures of Javanese compound words found in Panjebar Semangat magazine based on position of modifier? and (2) what are the equality of component meaning of Javanese compound words found in Panjebar Semangat magazine?The writer used qualitative approach and document analysis in conducting the study. The data were obtained from cerkak rubric in Panjebar Semangat magazine containing Javanese compound words. The analysis was based on the theory from Soepomo (1979).This study reveals that 32 Javanese compound words are found in cerkak rubric of Panjebar Semangat magazine. Based on the position of modifier and word class, the writer found 12 words belonging to head preceded by modifier, 5 words belonging to modifier preceded by head, 13 words belonging to the first word which has equal position with the second word. However, there are some unique forms which are different from the form of position of modifier generally that is one of the words performs as a supporting word and most of them do not have a classification of word. Besides, the writer found 3 classification of equality of meaning. There are 13 words belong to the first component has the same meaning with the second component, 4 words belong to the first component has the contradicted meaning with the second component, and 15 words belong to the last equality of component meaning which is there is no relation between the first component and the second component.The writer suggests the next researchers who are interested in conducting a research in similar topic are expected to use different objectives, such as the function, the usage etc. Moreover, the next researchers are expected to use other theories concerning the idea of Javanese compound word.